(3GdVQGFH Ydi GdONd GdGLeGdj (BI.R.G :s (3MSH JYOjdGJ bGfhf GdeGdjI (B2010 (3dWdHI GdeYGgO GdYdjG h GdLGeYGJ h cd GdeNJUjf GdGbJUGOjjf (B/s - (3Hf GYeGQI, efUhQs ((3GdLRGFQ(B: s (3OGQ gheg(B, s, 2011)
1)(3GdJPcjQ HGdJWhQ GdJGQjNj ddVQGFH aj GdLRGFQ (B: (3JYQja GdVQGFH GdeHGTQI h GdVQGFH ZjQ GdeHGTQI (B2)(3GdVQjHI Ydi GdONd GdGLeGdj HUaI YGeI h GdaFGJ GdSJ GdJj JJchf efgG GdVQjHI Ydi GdONd h ge cGdJGdj (B: (3GdGQHGM GdUfGYjI Ch GdJLGQjI h GdMQajI , CQHGM Gdegf ZjQ GdJLGQjI , eOGNjd GdGSJZdGdGJ GdRQGYjI , GdeQJHGJ h GdCLhQ h GdefM h GdQHhY GdYeQjI , GdeOJNjd GdfGJLI Yf JCLjQ GdCedGc GdeHfjI h ZjQ GdeHfjI h eOGNjd QHhY QDhS GdGehGd GdefbhdI(B.s
Keywords: (3GdLGeYGJs; (3GdONds; (3GdVQGFHs; (3VQjHI GdONds; (3bGfhf GdeGdjI(B- (3GdLRGFQs